THE ROLE OF PLAY ACTIVITY IN THE COGNITIVE DEVELOPMENT OF EARLY CHILDREN - Mamajonova Mufazzalkhon Bakhodirjon kizi (International Journal of Literature and Language Studies, 2026)
The article analyzes the pedagogical and psychological role of play in the cognitive development of children of early age (from birth to 3 years). The article is based on Jean Piaget's theory of sensorimotor stages of development and Lev Vygotsky's views on the two main directions of play and activity in children's activities. The aim of the article is to determine the effect of manipulative, sensory and exploratory games of early age children on cognitive indicators such as attention, memory, problem solving and understanding of cause-and-effect relationships.